Right-Sided Congenital Diaphragmatic Hernia Caused by Hepatopulmonary Fusion - Sonal Patel; Jennifer Rael (Case Reports in Pediatrics)
Introduction. Hepatopulmonary fusion is a very rare finding associated with right-sided congenital diaphragmatic hernia. With less than 50 reported cases, management and outcomes of hepatopulmonary fusion are poorly understood. This report highlights that clinical presentation is not a reliable indicator of outcomes in this rare disease. Case Presentation. A term neonate admitted for tachypnea and complete opacification of the right hemithorax was diagnosed with right-sided congenital diaphragmatic hernia. Preoperative respiratory support was minimal, and the only symptom exhibited was tachypnea. During surgical repair, fusion of the lung and liver were noted, consistent with a diagnosis of hepatopulmonary fusion. Postoperatively, the patient’s pulmonary hypertension worsened and required extracorporeal membrane oxygenation. Conclusions. Many patients with hepatopulmonary fusion and only mild symptoms die postoperatively from severe pulmonary hypertension and progressive respiratory failure. Preoperative clinical status is not indicative of postoperative outcomes, and literature suggests that patients who require less support preoperatively have high mortality rates. The availability of ECMO for postoperative complications may be necessary in patients requiring repair of hepatopulmonary fusion.